Penggunaan model pembelajaran two stay two stray (TSTS) berbantuan simulasi komputer untuk meminimalisasi miskonsepsi pada materi momentum dan impuls - Sutrisno, Asep Dedy; Samsudin, Achmad; Liliawati, Winny (WaPFi (Wahana Pendidikan Fisika), 2013)
Physics is one of the subjects that have a conditional concept for every level of the subject matter. Students are basically already had its own conception before studying physics. Conception of students may be same or different with concepts that are derived from the experts. Different conceptions can be said to be a misconception. Misconceptions can be identified by the diagnostic tests are multiple choice tests using a scale of Certainty of Response Index (CRI). This research aims to minimize the misconception of students on the concepts momentum and impulse with model of learning by using two stay two stray (TSTS) and computer-assisted simulations. This research method using quasi-experimental design with nonequivalent control group design involves two classes (experimental and comparison of each of the 37 students and 35 students) as a subject of research. Classroom interactive lecture using model comparison to compare the learning effectiveness in minimizing any misconception. The research results showed that: 1) profile of the popular high school students on the concepts momentum and impulse after learning of more than 20%, 2) learning model Uses two stay two stray (TSTS) and computer-assisted simulations can minimize the misconception by misconception results percentage of post-test up 21.3%, smaller than the comparison class with the grade percentage misconception results post-test of 40.2%, 3) Effectiveness of learning model-assisted computer simulation of TSTS is better than an interactive lecture model viewed from the value of the Normalized Gain such that both classes of 0.64 and 0.14.